Generalized Anxiety Disorder with Somatic Symptom Presentation and Social Avoidance: A Case Report - Alfiona Syafira Putri Arinda; Era Catur Prasetya (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Generalized Anxiety Disorder (GAD) is a psychiatric disorder that frequently presents with somatic complaints, which can lead to delayed diagnosis. This case report aims to describe the clinical manifestations, diagnostic process, and therapeutic response in a patient with GAD dominated by somatic symptoms. Case: A 63-year-old female patient presented with initial complaints of acid reflux sensation and epigastric pain since 2022. Medical examinations showed results within normal limits. The complaints progressed to palpitations, excessive anxiety, particularly in social situations, avoidance behavior, and sleep disturbances. The patient experienced a decline in social functioning, which subsequently improved after receiving pharmacological therapy and psychotherapy. Somatic symptoms in GAD are associated with autonomic nervous system activation and the brain–gut axis interaction. The diagnosis was established based on DSM-5-TR criteria, considering biopsychosocial aspects. Management using a combination of Selective Serotonin Reuptake Inhibitors (SSRIs) and Cognitive Behavioral Therapy (CBT) proved effective in improving the patient's symptoms and functioning.